Loot box purchases and their relationship with internet gaming disorder and online gambling disorder in adolescents: A prospective study - González-Cabrera, Joaquín; Basterra-González, Mª Aránzazu; Ortega-Barón, Jessica; Caba-Machado, Vanessa; Díaz-López, Adoración; Pontes, Halley M.; Machimbarrena, Juan Manuel (Computers in Human Behavior, 2023)
In recent years, the video game industry has introduced Loot Box (LB), a new type of microtransaction in which a gamer uses real currency to purchase a random virtual item within a video game. Recently, LBs became more widespread and there is evidence suggesting their similarity to online gambling. Although some studies have investigated the association between LBs with disordered gaming and disordered gambling, very few have done so with clinical indicators of these problems. Furthermore, to the best of our knowledge no longitudinal evidence of such relationships currently exists in the literature. Therefore, the present study aimed to 1) ascertain the stability of LB purchasing in minors and 2) investigate the associations between LB purchasing with gambling online and online gambling disorder within six months. A prospective cohort study was conducted at two time points six months apart. In total, 2.213 Spanish adolescents (1.067 [48.9%] boys) aged between 11 and 17 years participated in both waves. The purchase of LBs was prevalent and stable in the sample across the six months. While a positive relationship was found between purchasing LBs and online gambling six months later, the relationships between purchasing LBs and the presentation of online gambling disorder and gaming disorder require further study.
Keywords: gambling disorder; gaming disorder; longitudinal; loot boxes; microtransaction; prevalence; Scopus; JCR